Simulations of a photopumped X-ray laser using the H-like Cl-Li-like Se scheme - Al'Miev, I; Lu, X; Rose, S; Zhang, J; Wark, J (2004)
Calculations of the modal photon densities and gain in a photopumped Cl XVII-Se XXXII X-ray laser are presented. In this paper we undertake a realistic simulation of the generation of both Cl and Se plasmas, using a high-power optical laser, which includes radiation from both Ly-α fine-structure components of H-like Cl pumping the 2p3/2-5d5/2 transition in Li-like Se. The calculations are performed in two dimensions in a realistic geometry taking into account plasma gradients. This gives information about the spatial extent and time evolution of X-ray lasing gain on the 5-4 transitions (39.5 Å) in Li-like Se. We find that gain (about 200 cm-1) is expected only when the optical laser includes a pre-pulse. Calculations show that the absorption of pumping radiation in the pumped plasma can reduce the gain by 20%. Time-dependent calculations have shown that the gain is reduced by 30% in comparison to the steady-state calculations. The effect of the spectral profile and self-radiation of 5d5/2-2p3/2 transition in Li-like Se reduces the gain by about 2%. © 2003 Elsevier Ltd. All rights reserved.